Radiographic association of chronological age based on the root pulp and periodontal ligament visibility in lower second molar teeth in a subset of the Pakistani population - Mahwish Sami; Sarwat Memon; Fizza Saher; Qudsia Hassan (Journal of the Pakistan Medical Association, 2024)
Objective: To find radiographic association of the root pulp visibility and periodontal ligament visibility stages of lower second molar teeth with chronological age. Method: The prospective, analytical, cross-sectional study was conducted after approval from the ethics review committee of Ziauddin University, Karachi, and comprised digital orthopantomograms from 2020 to 2022. The orthopantomograms related to lower second molar teeth from the left side of the mandible of individuals of either gender aged 18-40 years. The orthopantomograms were subjected to stage classification to assess the radiographic root pulp visibility and periodontal ligament visibility of the lower second molar teeth. Data was analysed using SPSS 25. Results: Of the 260 orthopantomograms, 140(53.8%) belonged to female subjects and 120(46.2%) to male. The overall median age of the subjects was 24 years (interquartile range: 7 years). There were 164(63.1%) subjects aged 18-25 years, 70(26.9%) aged 26-33 years, and 26(10%) aged 34-40 years. A positive correlation was noted between age and stages of radiographic root pulp visibility and periodontal ligament visibility (P<0.05). The individuals found at stages 0 and 1 for root pulp visibility were aged at least 18 years, and for stage 2, the corresponding value was 21 years. For periodontal ligament visibility, the minimum age for stage 0 was 18 years, while for stages 1 and 2, the corresponding values were 21 and 25 years. Conclusion: Lower age was found to be associated more with stage 0 of root pulp visibility and periodontal ligament visibility. Key Words: Panoramic radiography, Periodontal ligament, orthopantomography, Dental pulp.